What is the constant term in the expansion of ( y 3 2 − y 3 1 + 1 y + 1 − y − y 2 1 y − 1 ) 1 0 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice problem! It involves multiple aspects of algebra.
Hey, it is an AIEEE (JEE MAINS) problem!
Problem Loading...
Note Loading...
Set Loading...
Using the identity a 3 + b 3 = ( a + b ) ( a 2 + b 2 − a b ) , we have y 3 2 − y 3 1 + 1 y + 1 = y 3 1 + 1 Also, using the identity a 2 − b 2 = ( a − b ) ( a + b ) , we have y − y 2 1 y − 1 = y − 2 1 + 1 Thus, all we have to do is find the constant term in the expansion of ( y 3 1 − y − 2 1 ) 1 0 . From binomal theorm, we have the r th term as ( r 1 0 ) ( − 1 ) 1 0 − r y 3 r − 2 1 0 − r . Since for a constant term, the power of y is zero, we must have 3 r − 2 1 0 − r = 0 ⇒ r = 6 Thus, the constant term is ( 6 1 0 ) = 2 1 0